Results of multivariate GLM analysis with size (mean and maximum size) of nine prey species or prey species groups as dependent variable and beak volume, head volume, gizzards mass, body mass, sex of eiders together with year as explanatory variables. - Karsten Laursen (556576); Anders Pape Møller (7913618) (2021)
Results of multivariate GLM analysis with size (mean and maximum size) of nine prey species or prey species groups as dependent variable and beak volume, head volume, gizzards mass, body mass, sex of eiders together with year as explanatory variables.